Pengorganisasian dan Pengelolaan Sampah di Pantai Jimbaran - I Made Suidarma; I Komang Dicky Tri Denis; I Nyoman Arta Yasa (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2022)
The garbage on Jimbaran Beach poses a serious ecological problem because it causes pollution and has disrupted beauty and health. Jimbaran Village Beach is a beach tourism area that needs to be managed properly, considering that tourist visits have started to increase so that the potential for waste disposal is also increasing. This service activity seeks to (a) raise awareness and the active role of the community in environmental conservation and (b) increase community self-reliance through waste management. The solutions and methods applied are participatory. The community, as the main actor in healthy environmental action, processes waste into products of economic value. The results of service activities show the formation of community mindsets and behavior in waste management based on the 3R concept (reduce, reuse, and recycle). Waste is processed into organic fertilizer with the help of waste processing equipment. The community becomes skilled in processing organic waste into fertilizer that can be used in the agricultural industry.